The Effect of Counseling on Clean and Healthy Behavior (PHBS) in Increasing Knowledge, Attitudes and Actions for Students of SMA Negeri 1 Simpangempat, Karo Regency in 2022 - Susanti Br Perangin-Angin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Health is the most important role in human life. The purpose of this study is to influence counseling about PHBS. This research method is pre-experimental with one group pretest posttest design. The population is all students in class 1 A totaling 34 students and the total sample is total sampling. The results of the study showed that knowledge and attitudes were good as many as 34 people (100%) and less action before action, namely as many as 28 people (82%) and after counseling the action was lacking to 21 people (62%). There is an influence of counseling on action with the T-test formula with the result that the value of tcount is greater than ttable (6.068> 1.69236)